Economic assessment of energy efficiency measures - Bielienkova О.; Tsyfra, T.; Matsapura, O.; Ostapenko, I. (Ways to Improve Construction Efficiency, 2018)
This article proposes an approach to economic evaluation of energy efficiency of multifamily residential buildings, which includes only the cost calculation for every design solution, evaluation of energy saving and indicators of economic efficiency of investment projects (Tok, NPV, IRR), but also to analyze the sensitivity of the project.